2005
DOI: 10.1002/dei.21
|View full text |Cite
|
Sign up to set email alerts
|

The oral referential communication skills of hearing-impaired children

Abstract: This paper focuses on the oral referential communication skills of hearing-impaired (HI) children. A task based on that used with language impaired children by Leinonen and Letts (1997) Grammar (Bishop, 1989), which suggested that the detection and evaluation stages of Ackerman's (1983)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…However, it constitutes a bridge between laboratory read speech and natural spontaneous speech by introducing communicative intent in the speech produced, and enabling researchers to collect speech that is relatively consistent across talkers in terms of the style and lexical content of the speech produced. Referential tasks that share similarities with the diapix task, in that they involve a transfer of specific information between two talkers, are frequently used in studies of communication with clinical populations (e.g., Leinonen et al, 1997;Lloyd et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, it constitutes a bridge between laboratory read speech and natural spontaneous speech by introducing communicative intent in the speech produced, and enabling researchers to collect speech that is relatively consistent across talkers in terms of the style and lexical content of the speech produced. Referential tasks that share similarities with the diapix task, in that they involve a transfer of specific information between two talkers, are frequently used in studies of communication with clinical populations (e.g., Leinonen et al, 1997;Lloyd et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…the responses to the clarification requests consisted of expansions of the original utterance. In summary, previous research on requests for clarification in interaction involving children with CI has shown that these children use more clarification requests than children with normal hearing except from the study by Lloyd et al (2). One plausible reason for the contradictory results is that the children with NH in the study by Lloyd (2) were younger than the children with CI, while the two groups were of the same age in the other studies.…”
mentioning
confidence: 71%
“…In summary, previous research on requests for clarification in interaction involving children with CI has shown that these children use more clarification requests than children with normal hearing except from the study by Lloyd et al (2). One plausible reason for the contradictory results is that the children with NH in the study by Lloyd (2) were younger than the children with CI, while the two groups were of the same age in the other studies. However, the previous studies have only examined task oriented communication, and in the present study it will be investigated if the pattern is similar in everyday interaction.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…3 In contrast, children who are deaf or hard of hearing have been found to have delayed or deviant pragmatic skill development. [4][5][6][7][8][9] Researchers have hypothesized that these delays are due to insufficient access to daily discourse and the underlying linguistic structures that support it. Pragmatic language competence is critical in face-to-face communication, and better pragmatic language skills also have been associated with success in educational settings.…”
mentioning
confidence: 99%